The 2020 Ming K. Jeang awards for excellence in Cell & Bioscience - Yun-Fai Chris Lau (Cell & Bioscience, 2021)
Abstract Three articles published by the research groups led by Yun-Bo Shi of the National Institute of Child Health and Human Development, National Institutes of Health, USA; Aria Baniahmad of the Institute of Human Genetics, Jena University Hospital, Germany; and Kuanyu Li of the Nanjing University Medical School, China, have been selected as the recipients of the 2020 Ming K. Jeang Award for Excellence in Cell and Bioscience.